2013
DOI: 10.1179/2042618613y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic cancer mimicking mechanical low back pain: a case report

Abstract: Objective and Importance: The purpose of this report is to describe the clinical course of a patient referred to physiotherapy (PT) for the treatment of low back pain who was subsequently diagnosed with metastatic non-small cell carcinoma of the lung. Clinical Presentation: A 48-year old woman was referred to PT for the evaluation and treatment of an insidious onset of low back pain of 2 month duration. The patient did not have a history of cancer, recent weight changes, or general health concerns. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…We found two systematic reviews presented in 5 articles [13][14][15][16][17]. Furthermore, we found 2 narrative reviews [10,18], 7 prospective cohort studies [19][20][21][22][23][24][25][26], 9 retrospective cohort studies often collecting data from medical records [27][28][29][30][31][32][33][34][35], and 8 case reports [36][37][38][39][40][41][42][43]. Six studies provided diagnostic test accuracy data related to red flags for detection of malignancy for patients with LBP and were included in the assessment of diagnostic accuracy using the QUADAS-2 (Table 1) [20,21,22,24,26,29].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found two systematic reviews presented in 5 articles [13][14][15][16][17]. Furthermore, we found 2 narrative reviews [10,18], 7 prospective cohort studies [19][20][21][22][23][24][25][26], 9 retrospective cohort studies often collecting data from medical records [27][28][29][30][31][32][33][34][35], and 8 case reports [36][37][38][39][40][41][42][43]. Six studies provided diagnostic test accuracy data related to red flags for detection of malignancy for patients with LBP and were included in the assessment of diagnostic accuracy using the QUADAS-2 (Table 1) [20,21,22,24,26,29].…”
Section: Search Resultsmentioning
confidence: 99%
“…We found five case reports. Patients were a 69-year-old man that visited a chiropractor with LBP after a twisting movement [39]; a 73-year-old lady with LBP and severe band like pain in the abdomen referred to a spine centre [40]; a 48-year-old women referred to physiotherapy for LBP [41]; a 15-year-old girl who visited the paediatric emergency department [42] and a 54-year-old man consulting the physiotherapist complaining of LBP after a motor vehicle accident [43]. In all cases, history taking and clinical examination did not reveal red flags that warranted medical referral.…”
Section: Origin Of Red Flagsmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, telemedicine was an under-utilized form of delivering health care in the field of pediatric urology [10]. Prior studies have demonstrated successful telemedicine encounters for post-operative visits as well as for prenatal consultations on urologic conditions, most commonly including urinary tract dilation [5e7].…”
Section: Discussionmentioning
confidence: 99%
“…46 No specific blood test exists for detecting common MSK disorders, eg, low back pain, so it is therefore not surprising to see lower usage except for oncology where "MSK-like" pain can often manifest in the presence of bony metastases highly associated with breast, lung, and prostate cancer. 47 CBCs are ancillary tests that are routinely used to help detect conditions such as rheumatoid arthritis and the family of autoimmune rheumatic disorders. These latter populations are typically seen by rheumatologists, a specialty who were not categorized separately in the NAMCS public use files, and this may have ultimately impacted the accuracy of the prevalence of CBC tests across physician specialties.…”
Section: Discussionmentioning
confidence: 99%